Eksternalitas Keberadaan Pintu Tol Kota Baru terhadap Penyerapan Tenaga Kerja dan Pendapatan Pelaku Usaha di Kecamatan Sukarame, Kota Bandar Lampung - Aliffia Novrima Giana; Moneyzar Usman (Journal on Education, 2023)
Toll gates have several impacts, such as on the economic conditions of the community. The kota baru toll gate is one of the busiest toll gates on the Bakauheni-Terbanggi Besar section, and this has had various impacts and changes in the area around the toll gate. This study aims to analyze the differences in the level of employment and income levels of businessmen before the existence of toll booths and after,, at the kota baru toll gate along Jalan Ryacudu, Sukarame, Bandar Lampung City. In this research using descriptive quantitative method. With the Wilcoxon Signed Rank Test used in data analysis in this study. The results of this study indicate that descriptively there are differences before the existence of toll booths and after on all indicators, employment and income levels. Meanwhile, after conducting an in-depth analysis using the Wilcoxon signed rank test, no significant difference was found in the income level indicators of businessmen between before and after the kota baru toll gate.